2007
DOI: 10.1088/0031-9155/52/10/017
|View full text |Cite
|
Sign up to set email alerts
|

Initial investigation of a novel light-scattering gel phantom for evaluation of optical CT scanners for radiotherapy gel dosimetry

Abstract: There is a need for stable gel materials for phantoms used to validate optical computerized tomography (CT) scanners used in conjunction with radiation-induced polymerizing gel dosimeters. Phantoms based on addition of light-absorbing dyes to gelatine to simulate gel dosimeters have been employed. However, to more accurately simulate polymerizing gels one requires phantoms that employ light-scattering colloidal suspensions added to the gel. In this paper, we present the initial results of using an optical CT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Polymer gel dosimeter is an emerging system and serves as good tool for dose verification in radiotherapy [1,2]. Absorbed dose and the dose can be extracted from different techniques such as Magnetic Resonance Imaging (MRI) [3][4][5], Optical Computed Tomography (Optical CT) [6,7], X-ray CT [8,9], Ultrasound CT (UCT) [10][11][12] and vibrational spectroscopy [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer gel dosimeter is an emerging system and serves as good tool for dose verification in radiotherapy [1,2]. Absorbed dose and the dose can be extracted from different techniques such as Magnetic Resonance Imaging (MRI) [3][4][5], Optical Computed Tomography (Optical CT) [6,7], X-ray CT [8,9], Ultrasound CT (UCT) [10][11][12] and vibrational spectroscopy [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, different imaging modalities applied for the readout and analysis processes are used. These include Magnetic Resonance Imaging (MRI) [2], Optical Computed Tomography (opt-CT) [3], x-ray CT [4] and Ultrasound [5]. Amongst them, MRI is an established methodology as a readout process in polymer gel dosimetry [6].…”
Section: Introductionmentioning
confidence: 99%
“…Both polymer gels [4] and PRESAGE [5,6] radiochromic plastic dosimeter, in conjunction with optical CT scanner [7,8], have been employed to verify 3-D dose distribution for complex treatments with photon beams, such as IMRT and stereotactic radiosurgery [9,10]. These studies have shown promising results in providing a 3-D dosimetry tools for photon external beam treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed three-dimensional dosimetric information for a proton beam is crucial for accurate treatment planning design and treatment delivery due to the sharp dose falloff at the end of the beam range and laterally at the field edges [1][2][3]. It is more challenging to measure the 3-D dose distribution of a pencil beam (1 -1.5 cm diameter) because of its small field size as well as the complexity of dose changes in various directions.Both polymer gels [4] and PRESAGE [5,6] radiochromic plastic dosimeter, in conjunction with optical CT scanner [7,8], have been employed to verify 3-D dose distribution for complex treatments with photon beams, such as IMRT and stereotactic radiosurgery [9,10]. These studies have shown promising results in providing a 3-D dosimetry tools for photon external beam treatments.…”
mentioning
confidence: 99%